2013
DOI: 10.1111/his.12262
|View full text |Cite
|
Sign up to set email alerts
|

Total submission of pelvic lymphadenectomy tissues removed during radical prostatectomy for prostate cancer increases lymph node yield and detection of micrometastases

Abstract: Submission of all pelvic lymphadenectomy tissue for histological examination improves the yield of lymph nodes and the detection of metastatic prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…In one population-based study with a 10-year follow-up, patients undergoing excision of at least 10 nodes (node-negative patients) had a lower risk of prostate cancer-specific mortality at 10 years than those who did not undergo lymphadenectomy (15). However, the number of dissected lymph nodes is considered to be a secondary result, as the number of dissected lymph nodes is also affected by pathological examinations (20), and the secure removal of connective tissue including the lymph nodes in the dissection area is likely to be more important than the number of dissected lymph nodes. An expansion of the pelvic cavity is required by urologists so that larger quantities of connective tissue, including lymph nodes, are able to be removed, and the dissection of connective tissues must be performed to the greatest extent possible, in order to eliminate localized microscopic metastases surgically.…”
Section: Extent Of Plnd ---------------------------------------------mentioning
confidence: 99%
“…In one population-based study with a 10-year follow-up, patients undergoing excision of at least 10 nodes (node-negative patients) had a lower risk of prostate cancer-specific mortality at 10 years than those who did not undergo lymphadenectomy (15). However, the number of dissected lymph nodes is considered to be a secondary result, as the number of dissected lymph nodes is also affected by pathological examinations (20), and the secure removal of connective tissue including the lymph nodes in the dissection area is likely to be more important than the number of dissected lymph nodes. An expansion of the pelvic cavity is required by urologists so that larger quantities of connective tissue, including lymph nodes, are able to be removed, and the dissection of connective tissues must be performed to the greatest extent possible, in order to eliminate localized microscopic metastases surgically.…”
Section: Extent Of Plnd ---------------------------------------------mentioning
confidence: 99%
“…A recent study by Perry-Keene et al 18 has shown that the mean number of lymph nodes was increased from 3.7 to 10.8 when all the tissue was embedded in pelvic lymphadenectomies. Deng et al reviewed whether enhanced detection of micrometastases in periprostatic tissue could be achieved using immunohistochemistry.…”
Section: Discussionmentioning
confidence: 98%
“…Using this approach, a single lymph node may be oversampled and also counted more than once, since several different pieces can be obtained by the pathologist, especially in the case of large lymph nodes, while small metastatic lymph nodes may be overlooked. To avoid this problem, a recent report suggested using a technique that involves submitting all nodal and perinodal tissue, and examining palpable lymph nodes and the remaining tissue separately 30 . Consistently with this view, in the light of our finding that ENE has a certain prognostic importance in PCa, and the fact that it may be a very focal aspect in a metastatic lymph node, we would emphasize the importance of examining the whole of each lymph node, however large.…”
Section: Discussionmentioning
confidence: 99%